Cucurbituril-mediated quantum dot aggregates formed by aqueous self-assembly for sensing applications. Issue 38 (24th April 2019) - Peveler, William J.; Jia, Hui; Jeen, Tiffany; Rees, Kelly; Macdonald, Thomas J.; Xia, Zhicheng; Chio, Weng-I Katherine; Moorthy, Suresh; Parkin, Ivan P.; Carmalt, Claire J.; Algar, W. Russ; Lee, Tung-Chun
Abstract : Supramolecular 'gluing' of quantum dots is demonstrated with cucurbituril and we present the opportunity to create molecular host–guest sensing schemes. Abstract : Self-assembled nanoparticles have important applications in energy systems, optical devices and sensors, via the formation of aggregates with controlled interparticle spacing. Here we report aqueous self-assembly of rigid macrocycle cucurbit[7]uril (CB[7]) and fluorescent quantum dots (QDs), and demonstrate the potential of the system for efficient energy transfer and sensing of small molecules.